Resistant fabric warming is a viable alternative to forced air warming to prevent inadvertent perioperative hypothermia during hemiarthroplasty in the elderly - Kümin, M; Jones, CI; Woods, A; Bremner, S; Reed, M; Scarborough, M; Harper, CM (Elsevier, 2021)
Background Surgical site infection (SSI) is associated with inadvertent perioperative hypothermia (IPH). This can be prevented by active patient warming. However, results from comparisons of warming techniques are conflicting. They are based mostly on elective surgery, are from small numbers of patients, and are dominated by the market leader, Forced Air Warming (FAW). Furthermore, the definition of hypothermia is debatable and systematic reviews of warming systems conclude that a stricter control of temperature is required to study the benefits of warming.